Case Report on Deep Brain Stimulation Rescue After Suboptimal MR-Guided Focused Ultrasound Thalamotomy for Essential Tremor: A Tractography-Based Investigation - Saluja, Sabir; Barbosa, Daniel A. N.; Parker, Jonathon J.; Huang, Yuhao; Jensen, Michael R.; Ngo, Vyvian; Santini, Veronica E.; Pauly, Kim Butts; Ghanouni, Pejman; McNab, Jennifer A.; Halpern, Casey H. (Frontiers in Human Neuroscience, 2020)
Essential tremor (ET) is the most prevalent movement disorder in adults, and can often be medically refractory, requiring surgical intervention. MRI-guided focused ultrasound (MRgFUS) is a less invasive procedure that uses ultrasonic waves to induce lesions in the ventralis intermedius nucleus (VIM) to treat refractory ET. As with all procedures for treating ET, optimal targeting during MRgFUS is essential for efficacy and durability. Various studies have reported cases of tremor recurrence following MRgFUS and long-term outcome data is limited to 3-4 years. We present a tractography-based investigation on a case of DBS rescue for medically refractory ET that was treated with MRgFUS that was interrupted due to the development of dysarthria during the procedure. After initial improvement, her hand tremor started to recur within six months after treatment, and bilateral DBS was performed targeting the VIM 24 months after MRgFUS. DBS induced long-term tremor control with monopolar stimulation. Diffusion MRI tractography was used to reconstruct the dentatorubrothalamic (DRTT) and corticothalmic (CTT) tracts being modulated by the procedures to understand the variability in efficacy between MRgFUS and DBS in treating ET in our patient. By comparing the MRgFUS lesion and DBS volume of activated tissue (VAT), we found that the MRgFUS lesion was located ventromedially to the VAT, and was less than 10% of the size of the VAT. While the lesion encompassed the same proportion of DRTT streamlines, it encompassed fewer CTT streamlines than the VAT. Our findings indicate the need for further investigation of targeting the CTT when using neuromodulatory procedures to treat refractory ET for more permanent tremor relief.